Residual Mitral Regurgitation After Repair for Posterior Leaflet Prolapse—Importance of Preoperative Anterior Leaflet Tethering. Issue 11 (1st June 2018) - Sakaguchi, Taichi; Kagiyama, Nobuyuki; Toki, Misako; Hiraoka, Arudo; Hayashida, Akihiro; Totsugawa, Toshinori; Tamura, Kentaro; Chikazawa, Genta; Yoshitaka, Hidenori; Yoshida, Kiyoshi
Abstract : Background: Carpentier's techniques for degenerative posterior mitral leaflet prolapse have been established with excellent long‐term results reported. However, residual mitral regurgitation (MR) occasionally occurs even after a straightforward repair, though the involved mechanisms are not fully understood. We sought to identify specific preoperative echocardiographic findings associated with residual MR after a posterior mitral leaflet repair. Methods and Results: We retrospectively studied 117 consecutive patients who underwent a primary mitral valve repair for isolated posterior mitral leaflet prolapse including a preoperative 3‐dimensional transesophageal echocardiography examination. Twelve had residual MR after the initial repair, of whom 7 required a corrective second pump run, 4 underwent conversion to mitral valve replacement, and 1 developed moderate MR within 1 month. Their preoperative parameters were compared with those of 105 patients who had an uneventful mitral valve repair. There were no hospital deaths. Multivariate analysis identified preoperative anterior mitral leaflet tethering angle as a significant predictor for residual MR (odds ratio, 6.82; 95% confidence interval, 1.8–33.8; P =0.0049). Receiver operator characteristics curve analysis revealed a cut‐off value of 24.3° (area under the curve, 0.77), indicating that anterior mitral leaflet angle predicts residual MR. In multivariate regression analysis, smaller anteroposterior mitral annular diameter ( P <0.001) and lower left ventricular ejection fraction ( P =0.002) were significantly associated with higher anterior mitral leaflet angle, whereas left ventricular and left atrial dimension had no significant correlation. Conclusions: Anterior mitral leaflet tethering in cases of posterior mitral leaflet prolapse has an adverse impact on early results following mitral valve repair. The findings of preoperative 3‐dimensional transesophageal echocardiography are important for consideration of a careful surgical strategy.